2009
DOI: 10.1177/1077801209347749
|View full text |Cite
|
Sign up to set email alerts
|

“How Would That Help Our Work?”: The Intersection of Domestic Violence and Human Rights in the United States

Abstract: This qualitative study explores whether individuals working within the domestic violence (DV) field in the United States have utilized a human rights framework and identifies potential benefits of this framework. Using the critique and experiences of women of color as a focal point, data were gathered through interviews with key individuals working with national and regional DV and human rights organizations. This article focuses on challenges within the mainstream DV movement and how a human rights approach c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Comprehension of the individuals' experiences makes us be able to see the world the same as the people whose experiences we have investigated see (Boswell & Cannon, 2014). Such comprehension will lead to the production of science and will help us actually understand the real worries of women who have experienced family violence as well as the spousal abuse phenomenon (Morgaine, 2011). Thus, the present research aims at recognizing and describing Iranian women's experiences of spousal abuse.…”
Section: Introductionmentioning
confidence: 97%
“…Comprehension of the individuals' experiences makes us be able to see the world the same as the people whose experiences we have investigated see (Boswell & Cannon, 2014). Such comprehension will lead to the production of science and will help us actually understand the real worries of women who have experienced family violence as well as the spousal abuse phenomenon (Morgaine, 2011). Thus, the present research aims at recognizing and describing Iranian women's experiences of spousal abuse.…”
Section: Introductionmentioning
confidence: 97%
“…Morgaine's (2011) research with diverse experts from IPV advocacy groups found that a human rights approach could strengthen the mainstream IPV movement in the United States-a movement that she argues has long grappled with issues of oppression, power, and privilege, especially in relation to racism. Specifically, Morgaine (2011) recommends making the IPV movement more holistic (addressing the complexity and intersectionality of concerns such as the survivor's economic, social, and cultural rights rather than focusing narrowly only on the immediate impact of the violence), more engaging of the community, and with expanded coalition building (including organizing across issues and engaging men as allies). Engaging with the community includes, in part, addressing human rights concerns from the bottom up (Morgaine, 2009) in a grassroots fashion.…”
Section: Resultsmentioning
confidence: 99%
“…For others, collective action or agency may be most therapeutic and consonant with the expression of their rights, such as participating in the collaborative campaign that resulted in the recent successful reauthorization of VAWA (Violence Against Women Reauthorization Act of 2013, 2013). Another example of collective agency is the 2002 Human Rights Tribunal on Domestic Violence and Child Custody, symbolically and strategically held at the Massachusetts State House on Mother's Day (Morgaine, 2011;Ford Foundation, 2004). Female survivors of DV documented the severe human rights violations against women and the Massachusetts family court's failure to protect women and their children from battering in the context of child custody matters (Ford Foundation, 2004).…”
Section: Core Principles Of a Rights-based Approach Appliedmentioning
confidence: 99%
See 2 more Smart Citations